The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3847/1538-4357/ab53d5
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation Histories of the LEGUS Dwarf Galaxies. III. The Nonbursty Nature of 23 Star-forming Dwarf Galaxies*

Abstract: We derive the recent star formation histories of 23 active dwarf galaxies using HST observations from the Legacy Extragalactic UV Survey (LEGUS). We apply a color-magnitude diagram fitting technique using two independent sets of stellar models, PARSEC-COLIBRI and MIST. Despite the non-negligible recent activity, none of the 23 star forming dwarfs show enhancements in the last 100 Myr larger than three times the 100-Myr-average. The unweighted mean of the individual SFHs in the last 100 Myr is also consistent w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 147 publications
1
31
0
Order By: Relevance
“…Older stars in Ho II are more centrally concentrated than younger stars (Bernard et al 2012), and this is consistent with the tendency for dwarf irregular galaxies to have recent star forming activity that is more diffusely distributed than at earlier epochs (e.g. Cignoni et al 2019).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Older stars in Ho II are more centrally concentrated than younger stars (Bernard et al 2012), and this is consistent with the tendency for dwarf irregular galaxies to have recent star forming activity that is more diffusely distributed than at earlier epochs (e.g. Cignoni et al 2019).…”
Section: Introductionsupporting
confidence: 60%
“…These galaxies have similar morphologies, integrated brightnesses, and distances. Cignoni et al (2019) find that dwarf irregular galaxies such as these tend to have had more or less constant SFRs during the past 100 Myr, with departures that are no more than 3× that from historic means, and so it is then expected that galaxies of this type will harbor intrinsically luminous LPVs and massive stars. Basic observational properties of these galaxies are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…This result is supported by SFH studies based on colormagnitude diagrams. NGC 4449 and NGC 3738 are found to have approximately constant SFHs in the last 200 Myr (Cignoni et al 2018(Cignoni et al , 2019Sacchi et al 2018). Sacchi et al (2019) also reported that the SFH of NGC 7793, which contributes 40% of our final sample (see Table 1), is not bursty and suggests inside-out star formation in this galaxy.…”
Section: Pahmentioning
confidence: 63%
“…It has a rich population of young, intermediate, and old star clusters, making it the best sampled dwarf galaxy in our study, potentially due to a rich star formation history sculpted by earlier interactions and mergers (see for e.g. Cignoni et al 2019). Whitmore et al (2020) include this galaxy in the recent H α-LEGUS survey that add narrowband H α imaging to a subsample of LEGUS galaxies, allowing the production of new cluster catalogs with improved ages.…”
Section: Ngc 4449mentioning
confidence: 99%